2015
DOI: 10.1158/1055-9965.epi-14-1017
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Associated with Gene Methylation in Estrogen Receptor–Positive Breast Tumors

Abstract: Background Although obesity is associated with breast cancer incidence and prognosis, the underlying mechanisms are poorly understood. Identification of obesity-associated epigenetic changes in breast tissue may advance mechanistic understanding of breast cancer initiation and progression. The goal of this study, therefore, was to investigate associations between obesity and gene methylation in breast tumors. Methods Using the Illumina GoldenGate Cancer I Panel, we estimated the association between body mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
3
30
0
Order By: Relevance
“…In a recent study of 345 breast cancer cases, the majority (87 %) of CpG sites analyzed showed elevated methylation in obese patients, particularly in estrogen receptor-positive tumors. Obesity was associated with the aberrant methylation of cancer-related genes involved with the immune response, cell growth, and DNA repair [22]. Several prior studies have compared DNA methylation in whole blood or peripheral blood leukocytes among obese and non-obese individuals [5860].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study of 345 breast cancer cases, the majority (87 %) of CpG sites analyzed showed elevated methylation in obese patients, particularly in estrogen receptor-positive tumors. Obesity was associated with the aberrant methylation of cancer-related genes involved with the immune response, cell growth, and DNA repair [22]. Several prior studies have compared DNA methylation in whole blood or peripheral blood leukocytes among obese and non-obese individuals [5860].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that certain environmental, behavioral, and demographic factors can influence the epigenetic state, which suggests that the behavioral factors associated with BE and EAC may act by inducing alterations in the methylation status of DNA [18]. For example, alterations in the methylation status of CpG islands in the promoter regions of genes implicated in obesity, appetite control, and metabolism have been shown to occur in DNA isolated from blood and breast tissue of obese compared to lean individuals [1922]. Tobacco smoking, meanwhile, has been associated with alterations in DNA methylation of multiple cancer-related genes in studies focused on single candidate genes as well as in genome-wide methylation studies of prostate cancer, the bronchial epithelium, and peripheral blood mononuclear cells [2326].…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical trial population, obesity is associated with inferior outcomes specifically in patients with hormone receptor-positive operable breast cancer [13]. Potential mechanisms for this link include increased estrogen production by adipose tissue, crosstalk between insulin or insulin-like growth factor and estrogen receptor signaling [27], obesity-associated hyper-methylation [28], and tumor growth-promoting adipokines [11, 29]. Association between obesity and poor survival outcome in breast cancer patients has been explained by predilection for advanced stage at diagnosis in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…To identify CpG loci that showed differential breast tumor methylation between cases who were active smokers versus never smokers, generalized linear regression models (GLM) were fitted to the logit transformed β -values adjusting for age (continuous), race (African American, white/other), menopausal status, stage (1, 2, 3, 4), body mass index (BMI) (<25, 25 to <30, ≥30 kg/m 2 ), and alcohol consumption (lifetime consumption in grams/week). BMI was considered a potential confounder as BMI differed between smoking groups and obesity (BMI ≥30) was previously associated with tumor methylation differences [42]. Similarly, alcohol consumption differed between smokers and never smokers and was previously correlated with breast tumor methylation patterns [43].…”
Section: Methodsmentioning
confidence: 99%